2020
DOI: 10.1186/s40560-020-00459-y
|View full text |Cite
|
Sign up to set email alerts
|

Development of a nomogram to predict 30-day mortality of patients with sepsis-associated encephalopathy: a retrospective cohort study

Abstract: Background: Sepsis-associated encephalopathy (SAE) is related to increased short-term mortality in patients with sepsis. We aim to establish a user-friendly nomogram for individual prediction of 30-day risk of mortality in patients with SAE. Methods: Data were retrospectively retrieved from the Medical Information Mart for Intensive Care (MIMIC III) open source clinical database. SAE was defined by Glasgow Coma Score (GCS) < 15 or delirium at the presence of sepsis. Prediction model with a nomogram was constru… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
54
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 55 publications
(56 citation statements)
references
References 51 publications
2
54
0
Order By: Relevance
“…[3] Fourth, except for lactate, RDW has the highest OR value in the multivariate logistic regression, indicating that it may signi cantly affect the prognosis of patients with suspected infection in ICU. This nding is consistent with some previous studies that RDW can be used to estimate the short-term mortality of nonhematologic diseases, such as sepsis-associated encephalopathy, [23] stroke, [24] cardiovascular diseases, [25,26] and liver diseases. [27,28] Studies had indicated that the in ammatory response and oxidative stress during sepsis may contribute to the adverse effect of RDW, [29][30][31][32] but the exact mechanisms under the relationship between RDW and the in-hospital mortality of patients with suspected infection are still unclear.…”
Section: Discussionsupporting
confidence: 92%
“…[3] Fourth, except for lactate, RDW has the highest OR value in the multivariate logistic regression, indicating that it may signi cantly affect the prognosis of patients with suspected infection in ICU. This nding is consistent with some previous studies that RDW can be used to estimate the short-term mortality of nonhematologic diseases, such as sepsis-associated encephalopathy, [23] stroke, [24] cardiovascular diseases, [25,26] and liver diseases. [27,28] Studies had indicated that the in ammatory response and oxidative stress during sepsis may contribute to the adverse effect of RDW, [29][30][31][32] but the exact mechanisms under the relationship between RDW and the in-hospital mortality of patients with suspected infection are still unclear.…”
Section: Discussionsupporting
confidence: 92%
“…Other study developed a predictive model that could provide an early risk assessment of sepsis in patients undergoing major hepatobiliary and pancreatic surgery (33). In addition, there are many prognostic models for sepsis patients, for example, one study constructed a predictive model of the 30-day risk of death in patients with sepsis-associated encephalopathy that could be used to assess their prognosis (34). Unlike these studies, to the best of our knowledge, we have constructed the first model that can predict the probability of sepsis in patients with UTI, based on the outcome of the patient's first laboratory examination and comorbidities.…”
Section: Figure 1 |mentioning
confidence: 99%
“…SAE in the study was de ned Glasgow Coma Scale (GCS) < 15, diagnosed delirium, or use of haloperidol in sepsis patients [3,12,13]. Consciousness disorder with clear causes were excluded.…”
Section: Patientmentioning
confidence: 99%
“…Excluded were patients [3,12]: 1) with brain injury (traumatic brain injury, meningitis, encephalitis intracerebral hemorrhage, cerebral embolism, ischemic stroke, epilepsy, or intracranial infection and another cerebrovascular disease) (Supplementary materials1-Supplementary materials5); 2) mental disorders and neurological disease (Supplementary materials6); 3) chronic alcohol or drug abuse (Supplementary materials7); 4) metabolic encephalopathy, hepatic encephalopathy, hypertensive encephalopathy, hypoglycemic coma, and other liver disease or kidney disease is affecting consciousness (Supplementary materials8); 5) severe electrolyte imbalances or glycemic disturbances, including hyponatremia (< 120 mmol/l), hyperglycemia (> 180 mg/dl), or hypoglycemia (< 54 mg/dl); 6) partial pressure of carbon dioxide (PaCO 2 ) ≥ 80mmHg; PaO 2 , S P O 2 have a nonlinearity relationship with the incidence and mortality of SAE patients. We used generalized additive models [15] to estimate the association between median PaO 2 , S P O 2 and sepsis with SAE, and elucidate the optimal PaO 2 , S P O 2 target in reducing the incidence of SAE patients and hospital mortality.…”
Section: Patientmentioning
confidence: 99%